IDENTIFIKASI KERAGAMAN SIFAT KUANTITATIF KAMBING MARICA DI KABUPATEN JENEPONTO (Identifcation of Quantitative Characteristic Diversity of Marica Goat in Jeneponto District) - F. Ashari; S.R. A. Bugiwati; L. Rahim; M.I. A. Dagong (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2017)
The research objective was to identify the population, spread characteristics, and quantitative characteristics of Marica goat in Jeneponto district in order to get more information about the morphological differences between the Marica goat and Kacang goat. The beneft of this research was to attain an accurate scientifc data on the population of spread character and quantitative characteristic of Marica goat. The outcome of the research can be utilized as references for government, researchers, and goat breeders in the preservation of Marica goat. This research was done by sampling the Marica goats at and Kacang goat as a comparison. The body dimensions were measured on body length, withers height, chest depth, hip height, chest girth, chest width, hip width, leg length, and body weight. The result showed that the Marica goat was only found around high altitude areas. The male Marica goat at 3-4 years of age was not found anymore. The total population of Marica goats recorded was 20 heads, and all of Marica goats have similarity in body dimensions with Kacang goats as an effect of uncontrolled breeding between Marica goat and Kacang goat. This experiment showed that there were no pure breed of Marica goat at Jeneponto district which is existing now. The homogeneity percentage of existing Marica goat was high (CV<20%), therefore it is not recommended to do the selection in that population